A decade of litigation regarding surgical informed consent in the Netherlands. Issue 2 (February 2019) - Veerman, M.M.; van der Woude, L.A.; Tellier, M.A.; Legemaate, J.; Scheltinga, M.R.; Stassen, L.P.S.; Leclercq, W.K.G.
Highlights: Deficient surgical informed consent is an important reason for litigation. Most patients felt not properly informed on postoperative complications. Alleged lack of informed consent is related to the occurrence of postsurgical complications. Success chances in informed consent related claims and complaints are high. Abstract: Objective: An inadequate surgical informed consent process (SIC) may result in a medical malpractice claim or medical disciplinary board (MDB) complaint. Aim of this study was to analyse characteristics of a decade of malpractice claims and MDB decisions regarding SIC in the Netherlands. Methods: A retrospective analysis of malpractice claims and MDB decisions concerning SIC disputes in four major surgical specialties was conducted based on company data from the largest medical malpractice insurance company and two public available online MDB databases. Results: A total of 11376 malpractice claims and 661 MDB complaints were filed between 2004–2013 and 676(6%) of these claims and 69(10%) of these complaints involved an alleged deficient SIC process. A random sample of 245(37%) claims and all MDB decisions were analysed. Reasons for filing a claim or complaint were insufficient counselling or recording of SIC elements. In 20% of lawsuits and 25% of claims the case resulted in favour of the complainant. Conclusion: A substantial portion of malpractice claims and MDB decisions is related to a deficient SIC process. Practice implications: Focusing on crucial SIC elements for patients may improve satisfaction and expectations and result in a lower risk for malpractice claims and MDB complaints.